The effect of neuropsychiatric medication on pediatric nonalcoholic fatty liver disease - Jamie L. Ryan; Ashley K. Sherman; Daniel E. Heble; Craig A. Friesen; James F. Daniel; Ryan T. Fischer; Voytek Slowik (Wiley, 2022)
Abstract Obese and overweight children are at risk of developing nonalcoholic fatty liver disease (NAFLD), which can lead to steatohepatitis, cirrhosis, and liver transplantation. Neuropsychiatric conditions affect an increasing proportion of children and often require neuropsychiatric medications (NPMs) that are associated with weight gain and/or drug‐induced liver injury. We sought to evaluate the role that the extended use of NPMs play in pediatric NAFLD. Medical chart review was conducted for 260 patients with NAFLD (NPM = 77, non‐NPM = 183) seen in the Liver Care Center at Children's Mercy Hospital between 2000 and 2016. Outcome measures included body mass index (BMI) percentile, BMI z‐score, aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin, and gamma glutamyltransferase, and were collected at diagnosis, 6-18 month follow‐up, and 18-36 months. Controlling for race and metformin, there was a significant increase over time in BMI z‐score (p < 0.01) and total bilirubin (p = 0.03), with only initial decreases in ALT (p < 0.01) and AST (p < 0.01). Except for higher total bilirubin in the non‐NPM group, no main effect of group or interaction effect was found. Similar patterns remained when subjects were analyzed by NPM drug class. Further study is needed to confirm these findings and to evaluate the effects of NPM dose and duration of exposure, by drug class, on pediatric NAFLD outcomes.